Maison du dauphin : maison fantôme pour une fonction dans l’ombre ? - Matthieu Lahaye (Bulletin du Centre de Recherche du Château de Versailles, 2006)
The Grand Dauphin did not have a house separate from the king. The latter had the upper hand not only due to accountancy, but also through the appointment of the various servants and domestics who took care of the prince in his daily life. But gradually, especially in the early eighteenth century with the expansion of his Meudon estate, the Dauphin was able to engage servants thanks to the increased revenue in his “coffers”. An informal house developed around him. Nevertheless we are forced to admit that his extreme financial dependence proves how the delphinal function during Louis XIV’s reign was truly under control.